Impaired Executive Functioning in Subclinical Compulsive Checking with Ecologically Valid Stimuli in a Working Memory Task - Harkin, Ben; Rutherford, Hannah; Kessler, Klaus (Frontiers in Psychology, 2011)
We previously showed that working memory performance of subclinical checkers can be affected if they are presented with irrelevant but misleading information during the retention period (Harkin & Kessler, 2009, 2010). The present study differed from our previous research in the three crucial aspects. Firstly, we employed ecologically valid stimuli in form of electrical kitchen appliances on a kitchen countertop in order to address previous criticism of our stimuli in terms of validity with respect to compulsive checking symptomatology. Secondly, we tested whether the new stimuli would allow us to employ a simpler (un-blocked) design while obtaining similarly robust results. Thirdly, in Experiment 2 we improved the measure of confidence as a metacognitive variable by using a quantitative scale (0-100), which indeed revealed more robust effects that were quantitatively related to accuracy of performance. The task in the present study was to memorise four appliances, incl. their states (on/off), and their locations on the kitchen countertop. Memory accuracy was tested for the states of appliances in Experiment 1, and for their locations in Experiment 2. Intermediate probes were identical in both Experiments and were administered during retention on 2/3 of the trials with 50% resolvable and 50% misleading probes. Experiment 1 revealed a general impairment of high checkers, which confirmed the efficacy of our stimuli. In Experiment 2 we observed the expected, more differentiated pattern: High checkers were not generally affected in their WM performance (i.e., no general capacity issue); instead they showed a particular impairment in the misleading distractor-probe condition. Also, high checkers’ confidence ratings were indicative of a general impairment in metacognitive functioning.